Jack London and White Fang: a lost struggle - Zilberstein, Gleb; Zilberstein, Svetlana; Rocco, Richard M.; Righetti, Pier Giorgio (Comptes Rendus. Chimie, 2022)
The California State Parks curators granted access to artifacts owned by Jack London that are in storage in their Sonoma Barracks in Sonoma, CA. A medicine case, drug vials, and various paper documents that covered the period of his life from 1906 to 1915 were examined for drug residues left on their surface. All the objects were tested with the non-invasive surface analysis EVA (ethylene-vinyl acetate) technology, which consist of a foil studded with ground mixed-bed cation/anion exchangers as well as with C$_{8}$ and C$_{18}$ resins. The harvested material collected by the foils was analysed via GC-MS and the following 12 drugs were identified: N-(4-ethoxyphenyl) acetamide, phenyl salicylic acid, morphine, 6-monoacetylmorphine, 3-acetylmorphine, diacetylmorphine, dipenteneglycol, quinine dihydrochloride, quinine base, atropine, scopolamine and hyoscyamine. Despite the claims by his biographers that he used opium, morphine, and heroin on a regular basis this assertion could not be confirmed by the chemical analyses of the objects here tested. Only two opioids were discovered, morphine and diacetylmorphine (heroin) both of which could have been derived from the use of common, legal (over-the-counter) flu and cough medications.